A comparative study of tea waste derived humic-like substances with lignite-derived humic substances on chemical composition, spectroscopic properties and biological activity - Raguraj, Sriharan; Kasim, Susilawati; Md Jaafar, Noraini; Nazli, Muhamad Hazim; Arachchige Amali, Rathnasekara Kuruppu (Springer, 2022)
Emerging demand for humic substances escalated the short supply of coal-related resources from which humic substances are extracted in large quantities for various applications. Production of humic-like substances from lignocellulosic waste materials similar in structural and functional properties to humic substances has gained interest recently. Tea waste is a by-product from tea manufacturing factories enriched in lignocellulose is used to extract two types of humic fractions. One fraction has purified humic-like acid (HLA), and the other has unpurified humic and fulvic acids called as humic-like substances (HLS). Elemental composition, spectroscopic (13C CPMAS NMR and FTIR) properties, and biological activity of tea waste derived humic-like substances (TWDHLS) were compared with commercially available humic acid (CHA) extracted from lignite. Elemental analysis and FTIR characterization showed slight differences between HLA and HLS, while NMR results revealed that both have similar carbon distribution and are abundant in cellulosic polysaccharides and lignin derivatives. The presence of more stable compounds in TWDHLS contribute to its recalcitrant nature. NMR spectra of CHA significantly varied with TWDHLS and were rich in aliphatic compounds. The biological activity of TWDHLS and CHA was studied at five different concentrations (0, 20, 40, 80, and 160 mg L−1). The results show that soil application TWDHLS at 80 mg L−1 concentration showed better results on the growth of tea nursery plants similar to CHA, contrasting to the variation in their structural properties. Our findings revealed that TWDHLS could be used not only as a potential plant biostimulant but also as a better substitute for humic substances.